THE USE OF GOOGLE CLASSROOM IN ENGLISH TEACHING AND LEARNING PROCESS AT SENIOR HIGH SCHOOL LEVEL - Nursyahrina, Herlia; Retami, Ledy H.; Pratama, Rika; Salsabil, Syahla Putri; Ihsan, Muhammad Taufik (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
The Covid-19 pandemic requires almost all human activity to move to digital media, including education services. Recently, education services must adapt to online learning methods. In response to these changes, many states, institutions, and organizations have been working on strategic plans to implement online education. The objective of this paper was to describe the usage of google classroom in the English teaching and learning process at the senior high school level. The method used in writing this paper was literature-based by collecting data and information that related to Google Classroom as a media for learning the English language. The results indicated that there are many advantages of using Google Classroom in implementing education in Indonesia are to enhance teachers' and students' ability to use technology wisely, particularly for learning processes, to save time, to be environmentally conscious, to overcome the distance of residence, to increase collaboration among students, to provide timeless communication, and to serve as secure document storage.